Gut microbiota dysbiosis induces neuroinflammation in major depressive disorders: mechanisms targeting the gut-brain axis - Li, Jiayi; Wan, Bei; Zhou, Le; Qian, Xin; Wang, Fushun; Gu, Simeng; Ma, Xianjun; Huang, Jason H. (Frontiers in Psychiatry, 2025)
Major depressive disorder (MDD) is a kind of mental disorder with high mortality, suicide and relapse rates, and might be the world's leading cause of health burden by 2030. Growing evidence suggests that neuroinflammation is closely linked to depressive pathogenesis and suggests that MDD can be called a microglia disease. And activation of the P2X7R/NLRP3 signaling pathway in microglia is a key mechanism causing nerve damage. In addition, it is recently found that gut microbiota might initiate neuroinflammatory processes underlying MDD, and gut microbiota dysbiosis can be affected by sleep to ameliorate neuroinflammatory processes. In this paper, we reviewed recent advances about gut-brain axis interactions with neuroinflammation, which might shed light on the mechanisms and treatment of depression.